Resiliencia y autoestima en estudiantes de la especialidad de Filosofía y Psicopedagogía de la Facultad de Educación UNAP, Iquitos 2024 - Vasquez Arevalo, Lery (2025)
The objective of this study was to determine the relationship between resilience and self-esteem in students of the Secondary Education program, specializing in Philosophy and Psychopedagogy, at the National University of the Peruvian Amazon, Iquitos, 2024. The research was basic in type, with a quantitative approach, non-experimental, cross-sectional, and correlational in scope. The population consisted of 100 students, who made up the census sample, to whom the Wagnild and Young Resilience Scale (1993) and the Rosenberg Self-Esteem Inventory (1965) were applied as data collection instruments. The results showed a high positive and statistically significant correlation between resilience and self esteem (Rho = 0,831; p < 0,001). Likewise, a strong relationship was found between personal competence and self-esteem (Rho = 0,814), as well as between self acceptance and acceptance of life with self-esteem (Rho = 0.820). These findings confirm that students with higher levels of resilience also demonstrate higher self esteem, highlighting the role of coping skills, perseverance, and self-acceptance as protective factors of psychological well-being. It is concluded that resilience is a key determinant in the construction and strengthening of self-esteem among Amazonian university students, making it necessary to promote institutional programs that reinforce self-worth and adaptive capacities in academic and social contexts.